Pedagogical possibilities of using AR effects in social networks (Gumilyov Journal of Pedagogy, 2026)
The article considers the pedagogical possibilities of using AR (augmented reality) effects in social networks as a tool for developing the digital literacy of university students and teachers in the higher education system. The relevance of the study is justified by the fact that in the conditions of digitalization, students actively use platforms such as Instagram, TikTok, Snapchat, but AR effects in this environment are mostly used for entertainment purposes and are little studied in terms of learning, visualization, creative content creation, and the development of digital security skills.The study is based on the methods of theoretical review and conceptual modeling. A theoretical review of scientific literature in the areas of digital literacy, media literacy, AR/VR in education, and social media studies was conducted, and a content and comparative analysis was conducted. AR platforms such as Spark AR and TikTok Effect House were examined through content analysis.The article presents a pedagogical model that explains AR effects in social networks as a tool for developing the informational, technical, creative and security components of digital literacy. Also, methodological recommendations and directions of educational scenarios for the integration of AR effects into the educational process for university teachers are identified. The results of the study can serve as a practical basis for improving educational programs for the formation of digital and media literacy in higher education institutions and organizing the educational process in a digital environment familiar to students.